THE POTENTIAL OF RAINFALL AND ITS IMPACT TO GROUNDWATER STORAGE IN JAVA ISLAND - Setyawan Purnama (Indonesian Journal of Geography, 2008)
The objectives of the study are to map the distribution of rainfall in Java, toanalyze its potential and the impact to groundwater storage. To achieve thosegoals, rainfall distribution is mapped using isohyet method. From the averagedistribution of monthly rainfall, the annual potential of rainwater on everywatershed was calculated. Afterwards, the groundwater storage was analyzed andcounted by applying the water balance concept. The results of the study show thatthe mean of the highest annual rainfall is 4082 mm which occurs on Cisadane-Ciliwung watershed and the lowest one is 1421 mm on Citarum Hilir watershed.From the rainfall potential, Cisadeg-Cikuningan watershed has the highest rainfallpotential at the amount of 25342 million m31month and Grindulu Panggulwatershed has the lowest potential at the amount of 3678 million m3lmonth.Meteorologically, Cisadeg-Cikuningan watershed has the highest groundwaterstorage at the amount of 6088 million m31yearand the lowest amount of it occurson Madura watershed at 78 million m3lyear.